Fazendo renda e tecendo a organização : um estudo sobre as práticas organizacionais da associação de renda irlandesa de Divina Pastora - Santos, Flávia Oliveira (2022)
The main attempts to transform handicrafts as a production system were found among primitive peoples, followed by groups that perform specific activities and even in contemporary times handicrafts play an important social role. Craft production is present throughout the national territory and is recognized as an important expression of local identity and Brazilian cultural diversity, enriching the national symbolic and artistic heritage. Within this context, we come across Irish lace, which is one of the most prominent handcrafted products in the state of Sergipe. Although it is produced in other locations, it is in Divina Pastora that there is the highest concentration of lacemakers and where the activity has greater socio-economic and symbolic importance and that we even find the largest Irish Lace Association in the state: ASDEREN. This research adopted the assumption that organizations are the result of practices and processes. And, in an attempt to cast this look at organizations, in this work, we seek to understand how ASDEREN organizes itself as a result of its practices and processes. As for the methodological procedures of this work, the approach was qualitative, descriptive and exploratory. The research strategy used was the biographical method, by analyzing the oral history of three ASDEREN lacemakers, whose data were collected through in-depth interviews, observation and field diary notes. Although we have proposed to overcome the dichotomous view of organizations, as main results some dichotomies emerged from the lacemakers' narratives: informality/formality; fragmentation/centralization and horizontality/verticality. It was identified that the studied organization oscillates between these dichotomies, but does all this together and at the same time. Here we understand a diverse, dynamic and multifaceted context.